2015
DOI: 10.1177/0269215515580600
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ expressed emotion and mood, rather than their physical disability are associated with adolescent adjustment: a longitudinal study of families with a parent with multiple sclerosis

Abstract: Citation: Bogosian, A., Hadwin, J., Hankins, M. and Moss-Morris, R. (2016). Parents' expressed emotion and mood, rather than their physical disability are associated with adolescent adjustment. A longitudinal study of families with a parent with multiple sclerosis. Clinical Rehabilitation, 30(3), pp. 303-311. doi: 10.1177/0269215515580600 This is the accepted version of the paper.This version of the publication may differ from the final published version. Permanent AbstractObjective. This study investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 39 publications
0
16
0
1
Order By: Relevance
“…Post-birth, chronic illness may limit mothers physically, financially, emotionally or cognitively, meaning that they have fewer resources and are less available to care for their child 37. In addition, parents’ emotional responses to their illness can predict children’s outcomes more strongly than the severity or duration of the illness,29 indicating the importance of appropriate family support services when a mother is chronically unwell. We accounted for parental mental illness in this study but did not specifically examine the association of co-occurring parental chronic physical and mental illness on children’s outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Post-birth, chronic illness may limit mothers physically, financially, emotionally or cognitively, meaning that they have fewer resources and are less available to care for their child 37. In addition, parents’ emotional responses to their illness can predict children’s outcomes more strongly than the severity or duration of the illness,29 indicating the importance of appropriate family support services when a mother is chronically unwell. We accounted for parental mental illness in this study but did not specifically examine the association of co-occurring parental chronic physical and mental illness on children’s outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…As chronic illness is associated with poor mental health,29 30 and comorbid parent physical and mental illness is associated with poorer child outcomes,9 29 a dichotomous variable indicating diagnosis/no diagnosis of mental illness for mothers and fathers (separately) was also included as a covariate. Parent mental illness diagnoses over the entire study period (identified as records with a ICD-10-AM ‘F’ code) were assembled from the HMDS and EDDC in addition to public outpatient data from the Mental Health Information System.…”
Section: Methodsmentioning
confidence: 99%
“…Some studies indicate an adverse impact including psychosocial problems (Bogosian, Moss‐Morris, & Hadwin, ), emotional immaturity, vulnerability (Razaz, Joseph, et al, ), social competences (Razaz, Nourian, Marrie, Boyce, & Tremlett, ), and an increased risk of mood or anxiety problems (Razaz, Tremlett, et al, ). A recent study using the strengths and difficulties questionnaire (SDQ) to measure psychosocial development confirms the association between mental health problems of parents with MS and increased internalizing and externalizing symptoms affecting their children (Bogosian, Hadwin, Hankins, & Moss‐Morris, ). Other studies find no adverse association of parental MS with children's development outcomes (Razaz et al, ) and no difference in overall difficulties between children of parents with MS and the general community (Steck et al, ), and some studies have shown an increase in prosocial behavior (Pakenham & Cox, ) and an increased feeling of being more empathic and grown‐up than peers (Bogosian, Moss‐Morris, Bishop, & Hadwin, ).…”
Section: Introductionmentioning
confidence: 88%
“…«Barn og unge påtar seg ofte et stort ansvar for sin syke forelder.» Det er mulig at foreldres håndtering av egen sykdom, i større grad enn den fysiske funksjonshemningen, påvirker barn og unges psykiske helse (7). Barn av MS-pasienter har lavere yrkesdeltakelse og økt behov for trygdeytelser (8).…”
Section: Konsekvenserunclassified